Where do you live and what do you do? Two questions that might impact your kidney health - Aoun, Mabel; Chelala, Dania (Frontiers in Nephrology, 2022)
In many cases the social determinants of health need to be assessed through their interaction with environmental factors. This review looks at the impact of physical location and occupation of individuals on their kidney health. It examines the effect of living at high altitude on kidney function and the relationship between extreme cold or hot temperatures and the incidence of kidney injury. It reviews as well the many occupations that have been linked to kidney disease in high-income and low-and-middle-income countries. As a conclusion, this overview proposes preventive recommendations that could be individualized based on weather, altitude, socio-economic level of the country and occupation of the individual.